2018
DOI: 10.1007/s10238-018-0505-6
|View full text |Cite
|
Sign up to set email alerts
|

Tight correlation between FoxM1 and FoxP3+ Tregs in gastric cancer and their clinical significance

Abstract: The aim of the present study was to investigate the expression of Forkhead box transcription M1 (FoxM1) and Forkhead box transcription P3 (FoxP3) in gastric cancer tissues in order to reveal any correlation between FoxM1, FoxP3 and clinicopathological parameters. Their clinical significance in gastric cancer was also investigated. Immunohistochemistry was used to detect the expression of FoxM1 and FoxP3 in gastric cancer and para-cancer tissues. The clinical significance of FoxM1 and FoxP3 in gastric cancer wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The functions of regulatory T cells (Tregs) in immune regulation is well known, and much is being made of their potential for PDCD1 based therapy [ 64 ]. Recently, researchers found that the expression of FOXM1 was positive correlated with FOXP3 (the specific molecular marker of Tregs) and FOXM1 may induce immune suppression via recruiting FOXP3 positive Tregs in cancer therapy [ 65 ]. These results highlight the therapeutic potential of FOXM1 in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of regulatory T cells (Tregs) in immune regulation is well known, and much is being made of their potential for PDCD1 based therapy [ 64 ]. Recently, researchers found that the expression of FOXM1 was positive correlated with FOXP3 (the specific molecular marker of Tregs) and FOXM1 may induce immune suppression via recruiting FOXP3 positive Tregs in cancer therapy [ 65 ]. These results highlight the therapeutic potential of FOXM1 in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that FoxP3 was upregulated in HCCA cells and FoxM1 bound to the FoxP3 promoter region to promote FoxP3 transcription. Similarly, both FoxM1 and FoxP3 were strongly expressed in gastric cancer, resulting in tumor metastasis, immune escape, and poor prognosis 21 . Our experiments revealed that the silencing of FoxP3 expression led to decreased levels of TGF‐β and IL‐6 as well as inhibited HCCA cell migration and invasion in case of adding Treg cells.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, a reduced number of regulating T-cells (Tregs) in the TME and reduced tumor size in immunocompetent mice were shown when combining thiostrepton to oxaliplatin [58]. Although the connection of FOXM1 to the TME is not yet well understood, it is suggested to play a role in T-cell differentiation and to affect the proliferation of macrophages [59,60]. Considering an important influence of immune cells in cancer development and treatment, tissue cultures display a vital immunological compartment [40,61], and thus might help to understand the complex FOXM1 network in context of the TME and the effects of thiostrepton by modulating immune activation.…”
Section: Discussionmentioning
confidence: 99%